Algoritmo de evolução diferencial aplicado no controle de força de um motor de indução linear - Soares, Matheus Garcia (2019)
This work presents an improvement of a non-sinusoidal wave control method, which has the objective of generating periodic variations of force in the shaft of a three-phase linear induction motors operating at speeds near zero. The improvement is performed through the application of a differential evolution algorithm for the determination of the supply voltage of induction motors without the use of an complex mathematical equation. For this, a computational model of the electric motor is developed to act as an evaluation function of the algorithm. The computational model was developed based on the traditional induction motor equations. The improvement of the method is validated through experimental tests, where the voltage applied to the motor is controlled by an FPGA connected to an inverter. The results show an improvement over previous work, finding optimal voltage values for different types of force profiles. Once proven the functionality of this improvement, its application can be extended to different types of electric machines.